A study on the crystal structure of palm oil-based whipping cream - Che Man, Y.B.; Shamsi, K.; Yusoff, M.S.A.; S., Jinap (AOCS Press, 2003)
The crystal structure of palm oil-based whipping cream was studied. Various proportions of refined, bleached, and deodorized palm oil (RBDPO) and palm kernel oil (RBDPKO) were prepared and their crystal structure and thermal profile were observed by an X-ray diffractometer and a differential scanning calorimeter, respectively. The results showed that all blends possessed a stable and shiny β' polymorph at 25 °C, which showed that RBDPO and RBDPKO were appropriate for producing a non-dairy whipping cream. Some eutectic effect was observed in some blends, which was attributed to the complex combination of TAG in RBDPO and RBDPKO.